A cosmopolitan dialect - Magqashela, Avela (University of the Free State, 2014)
It is estimated that, if nothing is done, half of 6000 plus languages spoken today will disappear by the end of this century (Unesco, 2009:online). With the disappearance of unwritten and undocumented languages, humanity would lose not only a cultural wealth but also important ancestral knowledge embedded, in particular, in indigenous languages. English has become the dominant language in the social and economic sectors of our society due to factors of globalization. Language carries an individual’s story and miscommunication of that story may result in a segregated community. This thesis is rooted in the idea of exploring the relationship between architecture and language. The project will focus on architecture’s ability to accommodate the transition of a sign to its representation and link with what is desired to be communicated. The proposed site (University of Free State campus) lies on the periphery of the campus, which has an accessible link to the public realm of the university. The proposed programme forms part of the universities’ agenda which focuses on the integration of the city into university life and the wider South African context. This project aims to act as a public interface of exhibitions for dialogue, lectures, and interpretation of languages.
Dissertation (M.Arch. (Architecture))--University of the Free State, 2014
Keywords: Indigenous languages; Representation; Architecture and communication